West Nile Virus, Argentina - Diaz, Luis Adrián (2008)
West Nile virus (WNV), genus Flavivirus, family Flaviviridaehas been rapidly dispersing through the Americas since its introduction in 1999 in New York (1). By 2004, serologic studies detected WNV-specific antibodies in birds and horses from Canada to northern South America (2-4). The first report of WNV activity in the Southern Cone of South America surfaced in April 2006, when 3 horses died in Argentina(5). However, established transmission foci in Argentina are unknown. We report evidence for the introduction and establishment of WNV in Argentina as early as January 2005.